Heteropolysaccharides from S. cerevisiae show anti-adhesive properties against E. coli associated with Crohn's disease. (1st November 2021) - Sivignon, Adeline; Yu, Shin-Yi; Ballet, Nathalie; Vandekerckove, Pascal; Barnich, Nicolas; Guerardel, Yann
Abstract: The Saccharomyces cerevisiae CNCM I-3856 was previously reported to strongly inhibit adherent-invasive Escherichia coli (AIEC) adhesion to intestinal epithelial cells in vitro and to favor AIEC elimination from the gut in a murine model of Crohn's disease in vivo . In order to identify which cell wall components of yeast are responsible for AIEC elimination, constituent polysaccharides of yeast were isolated and their anti-adhesive ability against AIEC adhesion in vitro was screened. A fraction containing mannan, β-glucan and α-glucan extracted from yeast cell-walls was shown to inhibit 95% of AIEC adhesion in vitro and was thus identified as the strongest anti-adhesive yeast cell wall component. Furthermore, this mannan-glucan-containing fraction was shown to accelerate AIEC decolonization from gut in vivo . This fraction could be proposed as a treatment to eliminate AIEC bacteria in patients with Crohn's disease, a microbial trigger of intestinal inflammation. Highlights: Mannan extracted from yeast inhibits E. coli adhesiveness to intestinal cells in vitro . A soluble fraction containing β-glucan/α-glucan/mannan (GGM) was extracted from S. cerevisiae cell wall. This soluble GGM fraction strongly inhibits E. coli adhesiveness to intestinal cells in vitro . This soluble GGM fraction favors elimination of E. coli from gut in vivo .